Analysis of the density of linear erosive features as a subsidy to the study of the landscape - de Andrade, Rafael Vilela [UNESP]; Lupinacci, Cenira Maria [UNESP] (Universidad de Jaen, 2023)
Erosive features can reveal or even denounce places where land use degrades soil quality. In order to identify and analyze these lands, a Density Map of Linear Erosive Features of a cuesta relief area in the municipality of Botucatu (Brazil) was elaborated. The analysis of the Linear Erosive Features Density Map (2010/2011) and the Land Use Map (2010/2011) showed that the highest density classes of erosive features are located on pastures, but are often triggered by runoff from urban areas or highways. Therefore, the map of density of linear erosive features proved to be an efficient instrument for landscape analysis, and could also contribute to the conservation of soils.
Análise da densidade de feições erosivas lineares como subsídio ao estudo da paisagem
Keywords: Cartography; Erosive dynamics; Land use; Landscape